2008
DOI: 10.1007/s00213-008-1159-y
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and amphetamine acutely cross-potentiate their behavioral and neurochemical responses in female Holtzman rats

Abstract: Overall, the present data demonstrate that acute interactions of nicotine and other psychomotor stimulants produce potentiative effects and that these transient interactions may play a role in the frequent co-use and abuse of nicotine and other stimulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 52 publications
1
33
1
Order By: Relevance
“…For example, nicotine exposure in adolescence has been shown to alter the rewarding effect of cocaine in adulthood [27]. Nicotine enhances locomotor activity to cocaine and activates other indirect dopamine agonists [28], [29]. However, these studies mainly focus on certain genes or neurotransmitters, and cannot understand the underlying mechanism from systems biology framework.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nicotine exposure in adolescence has been shown to alter the rewarding effect of cocaine in adulthood [27]. Nicotine enhances locomotor activity to cocaine and activates other indirect dopamine agonists [28], [29]. However, these studies mainly focus on certain genes or neurotransmitters, and cannot understand the underlying mechanism from systems biology framework.…”
Section: Discussionmentioning
confidence: 99%
“…Other behavioral effects associated with the interaction between nicotine and stimulants, such as cross-sensitization (a neurobiological adaptive process that is thought to play a role in the development and maintenance of addiction; [129]) have been demonstrated. These include interactions between nicotine and amphetamine [130], methylphenidate [131], cocaine [132], and METH [133]. Related neurobiological changes have also been noted in rodents pre-exposed to nicotine.…”
Section: Nicotine + Stimulant Interactionsmentioning
confidence: 99%
“…We previously reported that a single exposure to nicotine sensitizes locomotor responsiveness to other drugs of abuse, including AMPH, cocaine and methamphetamine. As compared to saline, a low dose of nicotine given to rats sensitized subsequent AMPH-induced locomotor behavior and AMPH-stimulated DA efflux in the striatum measured 1 to 4 hours later (Jutkiewicz et al, 2008), demonstrating a rapid sensitization following nicotine pretreatment. Conversely, an acute dose of AMPH rapidly enhanced locomotor behavior and DA efflux in response to nicotine (Jutkiewicz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%